The BES1/BZR1-family transcription factor MpBES1 regulates cell division and differentiation in Marchantia polymorpha - Mecchia, Martin Alejandro (2021)
Brassinosteroids (BRs) play essential roles in growth and development in seed plants;1 disturbances in BR homeostasis lead to altered mitotic activity in meristems2,3 and organ boundaries4,5 and to changes in meristem determinacy.6 An intricate signaling cascade linking the perception of BRs at the plasma membrane to the regulation of master transcriptional regulators belonging to the BEH, for BES1 homologues, family7 has been described in great detail in model angiosperms. Homologs of these transcription factors are present in streptophyte algae and in land plant lineages where BR signaling or function is absent or has not yet been characterized. The genome of the bryophyte Marchantia polymorpha does not encode for BR receptors but includes one close ortholog of Arabidopsis thaliana BRI1-EMS-SUPPRESSOR 1 (AtBES1)8 and Arabidopsis thaliana BRASSINAZOLE-RESISTANT 1 (AtBZR1),9 MpBES1. Altered levels of MpBES1 severely compromised cell division and differentiation, resulting in stunted thalli that failed to differentiate adult tissues and reproductive organs. The transcriptome of Mpbes1 knockout plants revealed a significant overlap with homologous functions controlled by AtBES1 and AtBZR1, suggesting that members of this gene family share a subset of common targets. Indeed, MpBES1 behaved as a gain-of-function substitute of AtBES1/AtBZR1 when expressed in Arabidopsis, probably because it mediates conserved functions but evades the regulatory mechanisms that native counterparts are subject to. Our results show that this family of transcription factors plays an ancestral role in the control of cell division and differentiation in plants and that BR signaling likely co-opted this function and imposed additional regulatory checkpoints upon it.